CORE ASPECTS OF DEVELOPING A MOBILE APPLICATION FOR SUPPLY CHAIN OPTIMIZATION AND ROLE-BASED MANAGEMENT OF INTERNAL TASKS - Ulyanovska, Yu. V.; Rudyanova, T. M.; Chuvanko, M. S. (Systems and Technologies, 2026)
The article examines approaches to the digitalization of internal business processes in retail and to the optimization of personnel management through the development of a mobile application with a multi-level access system. The aim of the study is to design and implement an architecture for a mobile application that provides differentiated access for employees, admin- istrators, and managers according to their roles and functional responsibilities. The paper analyzes modern task management solutions and defines requirements for developing a system intended to standardize and streamline internal operations within a retail network. The developed application enables centralized task creation, assignment, monitoring, and execution, as well as internal communication between personnel levels. Separate UI/UX interfaces have been designed for each user group to improve inter- action efficiency. The software implementation is based on C# and Blazor Server technologies, which made it possible to create a unified codebase for both mobile and web functionality. Data storage and processing are performed using Microsoft SQL Server Express, ensuring system scalability and information reliability. The scientific novelty lies in integrating hierarchical personnel subordination principles with access control mechanisms (ACL) in a mobile environment. The proposed solution enhances the operational efficiency of retail networks, optimizes internal workflows, and can be adapted for various organizational structures.